EFEKTIVITAS PENGELOLAAN ZAKAT OLEH BADAN AMIL ZAKAT NASIONAL KABUPATEN WAJO - Qasim, Dika Sastriani; Sastrawati, Nila (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2022)
This article aims to provide an overview of the effectiveness of zakat management by the National Amil Zakat Agency of Wajo Regency, the National Amil Zakat Agency (BAZNAS) of Wajo Regency, by using field research methods. Zakat management carried out by BAZNAS Wajo Regency, especially in collecting zakat has not shown maximum performance, it is marked by low community participation in distributing zakat through BAZNAS. Although there are supporting factors such as strengthening the legal basis of institutions through regional regulations, expediency, digitalization management, and transparency, the many obstacles faced such as the existence of BAZNAS that are not yet known by the public, budget and human resource limitations, community traditions or habits, and the lack of Zakat Collection Units (UPZ) and the large number of Amil Zakat Institutions (LAZ) formed by several Islamic Mass Organizations are the main causes of the ineffective performance of baznas of Wajo Regency, coupled with the level of public knowledge about the obligation to zakat, especially zakat maal which is still low.